The baby bump. Pregnancy’s new social visibility - Angela Biscaldi (Archivio Antropologico Mediterraneo)
This paper will offer several vantage points for interpreting a new social phenomenon: the flaunting of pregnancy in the public space, and in the media space in particular. In the last twenty years, the cultural meaning of pregnancy has been entirely upended: once a period of waiting, of suspension, almost mysterious and concealed, wrapped in prohibitions and fears, and surrounded by silence, pregnancy now seems to be something to be chronicled, savored and even exhibited by displaying the belly – painted or decorated – as if it were a trophy. Through thirty in-depth interviews with women in a range of occupations – midwives, photographers, belly painters and journalists – throughout Italy, we will attempt to explore the cultural meanings of this change.